Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/19490976.2019.1611151
|View full text |Cite
|
Sign up to set email alerts
|

Validation studies for germ-freeSmad3-/-mice as a bio-assay to test the causative role of fecal microbiomes in IBD

Abstract: While the association between microbiomes and inflammatory bowel disease (IBD) is well known, establishing causal relationships between the two is difficult in humans. Germ-free (GF) mice genetically susceptible to IBD can address this question. Smad3 -/mice with defective transforming growth factor ß signaling are a model of IBD and colon cancer. They develop IBD upon colonization with Helicobacter under specific pathogen-free conditions, suggesting a role of the microbiome in IBD in this model. Thus, we rede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The alarming rise in the incidence and prevalence of IBD in the industrialized world suggests that genetic factors only play a partial role in the development of IBD, and rapid changes in dietary and other environmental factors likely significantly contribute to this rise [9]. Moreover, under germ-free conditions (no microorganisms) animal models of IBD do not develop disease or the disease is significantly attenuated, suggesting that intestinal microbes are essential for the development of intestinal inflammation in IBD [10].…”
Section: Introductionmentioning
confidence: 99%
“…The alarming rise in the incidence and prevalence of IBD in the industrialized world suggests that genetic factors only play a partial role in the development of IBD, and rapid changes in dietary and other environmental factors likely significantly contribute to this rise [9]. Moreover, under germ-free conditions (no microorganisms) animal models of IBD do not develop disease or the disease is significantly attenuated, suggesting that intestinal microbes are essential for the development of intestinal inflammation in IBD [10].…”
Section: Introductionmentioning
confidence: 99%
“…High-income North America and high-income Asia Pacific showed the highest incidence and prevalence rates, which may be related to the risk factors of IBD. Although the pathogenesis of IBD is unclear, some studies have identified its risk factors [ 21 23 ]. For example, diet affects the development of IBD by altering the microbiota and modulating immune function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This allows researchers to isolate the effects of the gut microbiota on host physiology. Thirdly, germ-free animals provide a standardized experimental model that is highly reproducible, which facilitates comparisons across different studies ( Paik et al., 2020 ). Also, germ-free animals have reduced animal-to-animal variability compared to animals with complex microbiota, which increases the statistical power of experiments ( Wu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%